The effect of haptic cues on motor and perceptual based implicit sequence learning - Kim, Dongwon; Johnson, Brandon J.; Gillespie, R. Brent; Seidler, Rachael D. (Frontiers in Human Neuroscience, 2014)
We introduced haptic cues to the serial reaction time (SRT) sequence learning task alongside the standard visual cues to assess the relative contributions of haptic and visual stimuli to the formation of motor and perceptual memories. We used motorized keys to deliver brief pulse-like displacements to the resting fingers, expecting that the proximity and similarity of these cues to the subsequent response motor actions (finger activated key-presses) would strengthen the motor memory trace in particular. We adopted the experimental protocol developed by Willingham in 1999 to explore whether haptic cues contribute differently than visual cues to the balance of motor and perceptual learning. We found that sequence learning occurs with haptic stimuli as with visual stimuli and we found that irrespective of the stimuli (visual or haptic) the serial reaction time task leads to a greater amount of motor learning than perceptual learning.